A comparison of the attractiveness of flowering plant blossoms versus attractive targeted sugar baits (ATSBs) in western Kenya - Nick Yalla; Brian Polo; Daniel P. McDermott; Jackline Kosgei; Seline Omondi; Silas Agumba; Vincent Moshi; Bernard Abong’o; John E. Gimnig; Angela F. Harris; Julian Entwistle; Peter R. Long; et al. (PLoS ONE, 2023)
Attractive Targeted Sugar Baits (ATSB) have been demonstrated to result in significant reductions in malaria vector numbers in areas of scarce vegetation cover such as in Mali and Israel, but it is not clear whether such an effect can be replicated in environments where mosquitoes have a wide range of options for sugar resources. The current study evaluated the attractiveness of the predominant flowering plants of Asembo Siaya County, western Kenya in comparison to an ATSB developed by Westham Co. Sixteen of the most common flowering plants in the study area were selected and evaluated for relative attractiveness to malaria vectors in semi-field structures. Six of the most attractive flowers were compared to determine the most attractive to local Anopheles mosquitoes. The most attractive plant was then compared to different versions of ATSB. In total, 56,600 Anopheles mosquitoes were released in the semi-field structures. From these, 5150 mosquitoes (2621 males and 2529 females) of An. arabiensis, An. funestus and An. gambiae were recaptured on the attractancy traps. Mangifera indica was the most attractive sugar source for all three species while Hyptis suaveolens and Tephrosia vogelii were the least attractive plants to the mosquitoes. Overall, ATSB version 1.2 was significantly more attractive compared to both ATSB version 1.1 and Mangifera indica. Mosquitoes were differentially attracted to various natural plants in western Kenya and ATSB. The observation that ATSB v1.2 was more attractive to local Anopheles mosquitoes than the most attractive natural sugar source indicates that this product may be able to compete with natural sugar sources in western Kenya and suggests this product may have the potential to impact mosquito populations in the field.